Self-education in the Qur'an: The Prohibition of “Iltifat” as a Model - slamet riyadi; Abdel Aty, Ahmed (Prodi Pendidikan Bahasa Arab Sekolah Tinggi Agama Islam As-Sunnah, 2024)
Many stories in the Quran can be used as a guide in living life, in which educational values will always be relevant at any time, including the present. One is the